Effect of deep placement of N fertilizers on nitrogen use efficiency and yield of BRRI dhan29 under flooded condition (Asian Journal of Medical and Biological Research, 2018)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during boro season of 2016 to evaluate the effect of deep placement of nitrogen (N) fertilizers on N use efficiency and yield of BRRI dhan29 under continuous flooded condition. The soil was silt loam in texture having pH 6.27, organic matter content 1.95%, total N 0.136%, available P 3.16 ppm, exchangeable K 0.095 me%, available S 10.5 ppm and EC 348 μS cm-1. The experiment was laid out in a Randomized Complete Block Design (RCBD) with eight treatments and three replications. The treatments were T1 [Control], T2 [Prilled Urea, 130 kg N ha-1] , T3 [USG, 130 kg N ha-1], T4 [USG, 104 kg N ha-1], T5 [USG, 78 kg N ha-1], T6 [NPK briquette , 129 kg N ha-1], T7 [NPK briquette, 102 kg N ha-1] and T8 [NPK briquette, 78 kg N ha-1]. All the treatments except T6, T7 and T8 received 25 kg P and 64 kg K ha-1 as TSP and MoP, respectively. In T6, T7 and T8 treatments, P and K were supplied from NPK briquettes. Prilled urea was applied in three equal splits. USG and NPK briquettes were applied at 10 DAT and were placed at 8-10 cm depth between four hills at every alternate row. The results demonstrate that all the yield components except 1000-grain weight and yields of BRRI dhan29 responded significantly to the deep placement of N in the form of USG and NPK briquettes under continuous flooded condition. The highest grain yield of 6561 kg ha-1 was recorded in T3 [USG, 130 kg N ha-1] which was statistically similar to that ofT4 [USG, 104 kg N ha-1].The highest straw yield of 6876 kg ha-1 was obtained in T3 [USG, 130 kg N ha-1]. The lowest grain yield (3094 kg ha-1) and straw yield (3364 kg ha-1) were found for T1 (Control). The deep placement of USG and NPK briquettes enhanced the recovery of applied N and N use efficiency in comparison with the broadcast application of PU. The highest value of NUE (32.05 kg grain increase per kg N applied) was obtained in T5 [USG, 78 kg N ha-1] followed by T4 [30.75 kg grain increase per kg N applied) and the lowest value was found in T8 [130 kg N ha-1 from PU]. Based on yield, N use efficiency and cost-benefit analysis, an application of 104 kg N ha-1 as USG can be recommended as the best treatment for achieving satisfactory yield of boro rice (cv. BRRI dhan29) at BAU farm and at adjacent areas under AEZ 9 (Old Brahmaputra Floodplain).Asian J. Med. Biol. Res. December 2017, 3(4): 454-461